2022
DOI: 10.3390/cells11081302
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-like snoRNA-Derived RNAs (sdRNAs) Promote Castration-Resistant Prostate Cancer

Abstract: We have identified 38 specifically excised, differentially expressed snoRNA fragments (sdRNAs) in TCGA prostate cancer (PCa) patient samples as compared to normal prostate controls. SnoRNA-derived fragments sdRNA-D19b and -A24 emerged among the most differentially expressed and were selected for further experimentation. We found that the overexpression of either sdRNA significantly increased PC3 (a well-established model of castration-resistant prostate cancer (CRPC)) cell proliferation, and that sdRNA-D19b ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The TCGA database shows that there is deregulation of 38 specific sdRNAs in prostate cancer. The sdRNAs, D19 and A24, downregulate the tumor suppressor genes and promote proliferation, metastasis, and chemoresistance (Coley et al, 2022). The functions of snoRNAs are depicted in Figure 2.…”
Section: Generation Of Mirnas and Sdrnasmentioning
confidence: 99%
“…The TCGA database shows that there is deregulation of 38 specific sdRNAs in prostate cancer. The sdRNAs, D19 and A24, downregulate the tumor suppressor genes and promote proliferation, metastasis, and chemoresistance (Coley et al, 2022). The functions of snoRNAs are depicted in Figure 2.…”
Section: Generation Of Mirnas and Sdrnasmentioning
confidence: 99%
“…A study published in 2022 by our lab identified 38 specifically-excised and differentially-expressed sdRNAs in prostate cancer [ 73 ]. We began by querying PCa patient TCGA datasets alongside TCGA-normal prostate using an in-house web-based search algorithm SURFR (Short Uncharacterized RNA Fragment Recognition).…”
Section: Sdrnas In Cancermentioning
confidence: 99%
“…Further, five of these were significantly overexpressed in MDA-MB-237 compared to MCF7 breast cancer [ 72 ]. Most recently, in 2022, our lab similarly described 38 unique sdRNAs differentially expressed in prostate cancer patient samples [ 73 ] ( Table 2 ).…”
Section: Sdrnaomesmentioning
confidence: 99%
See 1 more Smart Citation
“…SnoRNAs can also act as the downstream molecule of p53 and MYC responsible for tumorigenesis [ 28 , 29 ]. Furthermore, a large group of sdRNAs is significantly associated with the characteristics of the tumor-immune microenvironment, and some of the sdRNAs function similar to the microRNAs involved in cancer progression and chemoresistance [ 30 , 31 ].…”
Section: Biological Functions Of Snornasmentioning
confidence: 99%